The Effect of Work Motivation and Job Satisfaction on Employee Engagement at Joglo Printing in Bekasi City - Luthfi Nur Ardyansyah; Indah Rizki Maulia; Adi Wibowo Noor Fikri; Rini Wijayaningsih (CV. Civiliza Publishing, 2026)
This research aims to determine the effect of work motivation and job satisfaction on employee engagement at Joglo Printing in Bekasi City. The type of research used in this study is quantitative research. The population in this study was 97 employees, the sampling technique used a saturated sampling technique through a questionnaire created via google form with respondent form all 97 Joglo Printing employees. The data analysis method used multiple linear regression. The data was processed using IMB SPSS Statistics 25. The results of this study indicate that (1) Work motivation has a significant effect on employee engagement at Joglo Printing in Bekasi City. (2) Job satisfaction has a significant effect on employee engagement at Joglo Printing in Bekasi City. (3) Work motivation and job satisfaction have a simultaneous effect on employee engagement at Joglo Printing in Bekasi City.